La naturaleza humana desde la perspectiva de la ciencia: una respuesta transhumanista a Elena Postigo - Gayozzo, Piero (2025)
In the article «Bioethics and transhumanism from the perspective of human nature», bioethicist Elena Postigo Solana presented an objection to the vision of human nature proposed by transhumanist philosophy. This objection was based on personalism, a philosophical framework according to which human nature is considered as dual, both physical and non-corporeal. This paper offers a response to Postigo's objection from a scientific philosophical framework, that is, from a perspective in continuous communication with the available scientific evidence. It is concluded that the idea of human nature developed by Postigo lacks empirical support, making the concept of human nature an empty one and typical of pseudosecular argumentation. Therefore, it is recommended to avoid the use of the concept of human nature in the bioethical discussion.